Comprensión lectora y su incidencia en el rendimiento académico a estudiantes de la Unidad Educativa “Rey David”, parroquia Camilo Ponce, cantón Babahoyo, provincia los Ríos. - León Riquero, Nolberto Elisalde (2018)
For what can be established in the development of the following research that reading comprehension, has been a subject studied from different perspectives, due to the importance it has in the learning process, affective and cognitive development of students, allowing them to be inserted in the society. Thus, as studies show that traditional educational models assume that the motivation of reading is measured by the amount of materials, time and exercises to the cognitive and affective aspects of the reading process. Reading comprehension is not only achieved with the simple fact that the student can decode accurately, but rather a task of great complexity in which different cognitive processes are involved from the visual perception of graphic signs to the construction of a semantic representation of its meaning. The ability that students have to understand difficult texts, which they use in the classroom is debatable, especially when it comes to scientific texts. The solution for this is to offer students relatively cohesive texts, establishing the best possible correlation between the reader and the text. School motivation is a general process by which a behavior towards the achievement of a goal is initiated and directed. This process involves both cognitive and affective variables: cognitive, in terms of thinking skills and instrumental behaviors to achieve the proposed goals; affective, insofar as it includes elements such as self-assessment, self-concept, etc.